On schurity of one-sided bimodule problems - Babych, V.; Golovashchuk, N. (Algebra and Discrete Mathematics, 2019)
We consider a class of normal bimodule problems satisfying some structure, triangularity and finiteness conditions (one-sided bimodule problems). We study the structure of non-schurian bimodule problems from our class and describe explicitly the minimal non-schurian one-sided bimodule problems.